APAKAH TAX SHIELD MEMENGARUHI TAX AVOIDANCE?: BUKTI EMPIRIS PERUSAHAAN PROPERTI REAL ESTATE DI BURSA EFEK INDONESIA - Diyana Diyana; Siti Nur Halisa; Ade Elza Surachman; Aditya Chandra (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
The dynamics of the property and real estate sector in Indonesia are facing inflationary pressures and surging construction costs that threaten developers’ profitability. These conditions have led companies to view taxes as a burden that erodes profits, causing management to exploit regulatory loopholes through tax avoidance practices. This study examines the influence of debt tax shields and non debt tax shields on tax avoidance. Using a quantitative method and a sample selected via purposive sampling, the study includes 41 companies listed on the Indonesia Stock Exchange for the years 2023–2025. The test results indicate that, both partially and simultaneously, debt tax shields and non debt tax shields have a positive and significant effect on tax avoidance, with an R-squared contribution of 29%. Optimal tax avoidance practices will maximize the utilization of tax shields from debt and non debt sources to reduce taxable income and avoid high corporate tax burdens. Thus, the measured use of tax shields within regulatory limits while maintaining tax compliance will strengthen the company’s financial stability.